Evaluating the experience of the state of Qatar in the Islamic Takaful Insurance industry as a pioneering model in the economies of Arab countries during the period (2013-2020) - Aboubaker Bossalem; Daoud Ghediri; Fateh Serdouk (Advanced Research in Economics and Business Strategy Journal)
This study aimed at diagnosing the reality of the Islamic Takaful Insurance industry at the global level, and evaluating the financial performance of Islamic Takaful companies in the State of Qatar, according to three criteria: policyholders' assets, policyholders' contributions, and insurance surpluses, then arranging them according to the best financial performance. This study concluded that Islamic Takaful Insurance constitutes a very small part of the Islamic finance industry (globally (2%), in Qatar (1%)). It also concluded that Islamic Takaful Insurance companies in the State of Qatar enjoy acceptable financial performance efficiency, topped by two companies: Islamic and Bema, followed by a lesser degree each of the Gulf and General Takaful Company, to come in the rank The latter is the Doha Takaful Company.